PEMBERDAYAAN UMKM JATINEGARA KAUM MELALUI KEGIATAN PENDAMPINGAN DAN BIMBINGAN PEMASARAN ONLINE - Safitri, Dini; Romli, Nada Arina (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2024)
Jatinegara Kaum Subdistrict has a program to empower UMKMs so they can advance to class. Unfortunately, the empowerment program is still less than optimal, especially in the product promotion section. The aim of this service activity is to empower Jatinegara Kaum UMKMs through online marketing activities. The method you use is a method of assistance and guidance to Jatinegara Kaum UMKMs so that they are empowered to use tools in online marketing applications. This activity will last for 5 months, namely from February-June 2024. The result of this activity is that there are 9 Jatinegara Kaum MSMEs that we assisted to be able to optimize Instagram social media by creating unique and easily recognizable MSME profiles. While we were assisting, there was optimization as shown by Instagram being active in making posts, and these posts were made every week. This makes Jatinegara Kaum UMKM products more widely known.